(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
While advancements in cancer therapy have increased concurrently, there is a greater awareness of the various dimensions of misery endured by individuals with cancer and those who care for them. In order to alleviate these suffering, palliative care physicians, researchers, and advocates have spent the last 50 years learning from and alongside cancer patients. As a result, they have become valuable collaborators with oncology physicians. An interdisciplinary team (IDT) approach, in which members from several disciplines work together to alleviate multidimensional pain and suffering and improve quality of life, is beneficial to patients with terminal illnesses in palliative care. Members of the psychosocial team are essential to the palliative care IDT because they offer knowledge of assessment and treatments for psychological distress that have been scientifically proven to work. This presentation will examine the various aspects of psychological discomfort that patients with advanced cancer may encounter. Effective relationships built on emotional attachment serve as the cornerstone of cancer patients’ palliative treatment. Given the configurations and environments of palliative care within health systems, training programs on techniques for building emotional bonds can be offered in order to effectively administer palliative care.